Empowerment and social and solidarity economy : case studies of women's organisations in West Africa - (:unkn) unknown (My University, 2015)
The objectives of this work are to analyse different practices of social and solidarity economy that enable African women to move beyond vulnerability. Income generating activities involve both an increase in individual and collective empowerment of women, and in addition - further development of their communities. African women are key agents of change through individual actions, but most of all - though collective once. In Africa, as well as in various countries of the South, female organisations are not only a place for women to gain some economic independence, but a genuine areas of freedom and exchange, that allow them to come out of isolation, to learn new skills, and to have more esteem and self-confidence as individuals in their own rights alongside the men in a patriarchal societies. It is through these activities that women strengthen their role, their social status, and reinforce their femininity and presence Women's organisations, in different degree, manage to gain some success. The positive impact of women's participation in these groups suggests that the individual or collective empowerment of poor women is possible by opting for alternative solutions based on practical and collective actions that develop more capacity and greater freedom. In this sense, Sen's capability approach is relevant to the extent, that it reinforces the importance of women's activities within the social economy, thereby strengthening the gains in terms of empowerment. The main function of female economic organisations is to enable women members to be able to support themselves through mobilisation and redistribution of resources and therefore help them out of poverty. These women who are active in organisations and are often responsible for the family, often seek most financial means to meet their family and social obligations. Through our work, we have identified further significant gains for women as individuals, as well as in a collective, but these gains are
Keywords: African Research